Philanthropy of Zakat for Santri Education Scholarship Program - Desiana, Rina; Ayumiati; Puan Maharani (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2025)
Zakat philanthropy plays an important role in alternative financing in Islamic educational institutions. This research aims to analyze the implementation and impact of zakat distribution for the scholarship program for Islamic boarding school students in Simeulue Regency. The research method used is qualitative, where data is obtained from interviews with informants consisting of the main informant from Baitul Mal Simeulue and 10 key informants who are zakat recipients from the program. The research results explain that the scholarship program helps alleviate the economic burden on parents and provides motivation for students to continue their education to a higher level. In terms of socio-economic impact, this program contributes to improving the quality of life for the beneficiaries and helps them rise above the poverty line. In addition, the existence of regular coaching and the implementation of a reward and punishment system for scholarship recipients encourages beneficiaries to maintain and improve their academic performance. This research can serve as a reference for the Zakat Management Organization in the management of zakat for education.